أصول التفسير عند ابن عاشور من خلال تفسيره التحرير والتنوير - يسمينة, مناعي; زينب, قرنيط; مفيدة, مناعي (جامعة الوادي-university of eloued, 2014)
This is note in he original of interpretation for tahar ben achour when he ATAHRIR WA TANWIR we find in it the important of topic and the way which we use; in adctition of that we subtract the general problem .... and others then we edncat: primally search : difinition of central terms. first search: the biography of tahar ben achour second search:resowces of interpretation conchision search arab science, archeology , arab news , principles of juriprudence , otophone and science readings :the most inportant result we obtained.